SCIENCE OF THE SELF AS DEPICTED IN THE STORY OF THE SNAKE-CATCHER: : RÅªMÄª â€™S MATHNAWÄª IN CONTEXT - Zekrgoo, Amir H.; Tajer, Leyla H. (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2016)
The self is always become a central concept in the mysticism tradition, nonetheless for JalÄl al-DÄ«n RÅ«mÄ« (d.1207). Through MathnawÄ«, RÅ«mÄ« uses metaphors to presents manâ€™s multi-layered self. He communicates through stories with great potential to be developed into various forms of visual and performing arts. Through his creative imagination, and using elements from Persian mystical literature RÅ«mÄ« presents his messages in an attractive and tangible form. Adopting metaphors and symbols he pictures various faces of nafs (self) relating each face to an individual animal. â€œThe Snake Catcherâ€™s taleâ€ is an excellent artistic display of manâ€™s battle with his animal self. It offers a complex religious subject in an easy-to-digest manner that can be visualized and set into play